Research on the Construction of Course Evaluation System Based on OBE Concept and the Background of Curriculum Thinking and Politics - Chunhui Wang; Zhenni Zhong; Guoyuan Che; Ping Wang; Tao Zhang (Journal of Advanced Research in Education, 2022)
Curriculum thinking politics is becoming more and more important in the ideological and political work of colleges and universities, and the development of engineering curriculum thinking politics is a difficult point in the process of promoting curriculum thinking politics in colleges and universities. In this paper, we selected the course of concrete structure design principles for research and analysis, and found that the course thinking politics of engineering majors is facing real difficulties such as insufficient attention, the cognitive bias, of course, thinking politics among teachers of professional courses, and the complexity, of course, thinking politics increased by the diversified development of students. Through the practice of the reform of the curriculum of the principle of concrete structure design, we summarize the paths of the effect of the curriculum of engineering courses in colleges and universities, deepen the importance of the curriculum of engineering courses, enhance the coupling of engineering professional education and the curriculum of political education, and provide reference significance for the curriculum of engineering majors to carry out the reform of the curriculum of political thinking.